Membumikan Nilai-Nilai Keadilan Dalam Al-Qur`An Terhadap Sila Keadilan Sosial - Hilmi Ridho (HUMANISTIKA : Jurnal Keislaman, 2021)
Abstract: Social justice is one of the five principles of Pancasila as the state ideology, with social justice will be formed peace and prosperity for the people of Indonesia. Social justice in Pancasila covers all aspects of people's lives. The government should apply social justice to all communities, both those residing in the domestic and public spheres, so as not to there are more people who feel they do not get justice in the form of their rights and interests. Poor attention to social justice, coupled with a lack of understanding of the meaning of justice in the Koran and the lack of efforts to implement justice from parties who have authority in the area. This paper is reviewed as a form of concern for people who have not obtained social justice rights, especially rural communities It is fitting that social justice is in line with the principle of justice in the Koran, so that the principle of social justice in pancasila is in line with the spirit of islamic teachings; both conceptually and praxis. Pancasila, which was supposed to embrace and become a shelter for Indonesians with its principles, has now backfired on their own. Abstrak: Keadilan sosial merupakan salah satu dari lima asas Pancasila sebagai ideologi Negara, dengan keadilan sosial maka akan terbentuk perdamaain dan kesejahteraan bagi masyarakat Indonesia. Keadilan sosial dalam Pancasila mencakup segala bidang aspek kehidupan masyarakat. Pemerintah seharusnya menerapkan keadilan sosial kepada seluruh masyarakat, baik yang bertempat tinggal di ranah domestik maupun publik, sehingga tidak ada lagi masyarakat yang merasa tidak mendapatkan keadilan berupa hak-hak dan kepentingannya. Miskinnya perhatian keadilan sosial, dibarengi dengan kurangnya memahami makna keadilan dalam Alquran dan tidak adanya upaya implementasi keadilan dari pihak-pihak yang memiliki otoritas di daerah tersebut. Tulisan ini dikaji sebagai bentuk kepedulian atas masyarakat yang belum mendapatkan hak-hak keadilan sosial terutama masyarakat pedalaman. Sudah sepatutnya keadilan sosial selaras dengan prinsip keadilan dalam Alquran, agar asas keadilan sosial dalam pancasila sejalan dengan spirit ajaran-ajaran agama Islam; baik secara konseptual maupun praksis.